The Influence of Service Quality, Store Atmosphere, and Price on Consumer Satisfaction at Gosha Kitchen & Patisserie Renon Denpasar, Bali, Indonesia (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates the influence of service quality, store atmosphere, and price on consumer satisfaction at Gosha Kitchen & Patisserie Renon, Denpasar. The rapid growth of culinary businesses in Bali has intensified competition, making consumer satisfaction a critical success factor. This research employs a quantitative approach using accidental sampling with 100 respondents from a population of 105,970 consumers. Data analysis techniques include validity testing, reliability testing, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, and hypothesis testing (F-test and t-test). The results demonstrate that: (1) service quality, store atmosphere, and price simultaneously have a positive and significant effect on consumer satisfaction; (2) service quality partially has a positive and significant effect on consumer satisfaction; (3) store atmosphere partially has a positive and significant effect on consumer satisfaction; and (4) price partially has a positive and significant effect on consumer satisfaction. The findings suggest that improving service responsiveness, enhancing visual communication through attractive menu designs and clear signage, and maintaining price transparency compared to competitors can significantly increase consumer satisfaction. This research contributes to the marketing management literature by providing empirical evidence from the Indonesian culinary industry context.